The Use of Open Educational Resources during the COVID-19 Pandemic: A Qualitative Study of Primary School Mathematics Teachers in Hong Kong - Chung-Kwan Lo; Ahmed Tlili; Xiaowei Huang (Education Sciences, 2022)
During the COVID-19 pandemic, teaching and learning activities had to be conducted fully online. To sustain quality education, teachers could use open educational resources (OERs) available in the public domain to make online mathematics teaching more effective and interactive. However, we currently know little about the use of OERs in primary school settings. Therefore, this study seeks to understand their school policies and guidelines on and teachers’ experience of using OERs during the pandemic. Our overarching goal is to provide recommendations on the future development and use of OERs in the context of primary school mathematics education. We employed a qualitative approach and interviewed 13 mathematics teachers from different primary schools. Our findings suggest that teachers tended to rely on OERs more during the pandemic than before. They used OERs to introduce mathematics and to facilitate class interactions in online lessons. However, not all schools had policies and guidelines on the use of OERs in place. Some teachers also encountered challenges when using OERs, such as finding that the resources were unsuitable for school contexts and lower primary school students. Based on the findings, we discuss some possible strategies for the improvement, such as ensuring the suitability of OERs, through developer–teacher collaborations.